Comparative analysis of entrepreneurial intentions among generations in Jambi Province: A study of Gen Bust, Millennials, and iGeneration - Junaidi, Junaidi; Hardiani, Hardiani; Hastuti, Dwi (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2024)
In the face of intense global competition, such as the introduction of the ASEAN Economic Community (AEC), the Indonesian workforce must transition from merely seeking employment to creating job opportunities. In this regard, cultivating an entrepreneurial spirit is a strategic alternative to bolster employment prospects and stimulate innovation. This study was carried out in the province of Jambi with the primary objectives of: 1) analyzing the characteristics and entrepreneurial intentions across different generations in Jambi; 2) examining the factors that influence these entrepreneurial intentions. The research compares three generations—Generation Bust (Gen Bust), Millennials, and the iGeneration—all within the productive age bracket and possesses substantial potential to drive development. The research methodology entailed collecting data through surveys administered to individuals from Gen Bust, Millennials, and the iGeneration in Jambi. The data was analyzed using descriptive statistical tools and the Structural Equation Modeling (SEM) technique. The findings reveal notable differences in entrepreneurial intentions among the generations, with Gen Bust and Millennials exhibiting stronger entrepreneurial intentions than iGeneration. Influential factors for these entrepreneurial intentions include attitudinal and contextual elements such as academic, social, and environmental support. Although individual characteristics vary among the generations, they do not consistently exert a direct and significant impact on entrepreneurial intentions, particularly for iGeneration. This research offers crucial insights into how specific factors affect entrepreneurial intentions across different generations, which can assist in developing strategies and policies to foster entrepreneurship in Jambi, especially in light of global and regional economic challenges.